ANALISIS MOTIVASI BELAJAR PADA KETERAMPILAN MENYIMAK SISWA KELAS III SDS MUHAMMADIYAH 06 TEBET - Fadhilah, Jihan; Ritonga, Rudi (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
The background of this reseacrh is that the researchis wants to know and describe further about the analysis of learning motivation on the listening skills of third grade students of SDS Muhammadiyah 06 Tebet. This study aims to analyze the learning motivation of the grade students of SDS Muhammadiyah 06 Tebet, explain how the learning process in analiyzing the learning motivation of the third grade students of SDS Muhammadiyah 06 Tebet is listening and what factors can incrase learning motivation and teacher efforts to maintain qualitu. Learning motivation on students: listening skills. The results of the study show that the learning process in the analysis of learning motivation on students’listening process in the analysis of learning motivation on stundents’ listening skills is carried out using the Google Meet aplication, WhatsApp group and the Kejar Cita website. Factors that can increse learning motivation in students’ listening skills, there are 2 motivations, namely instrinsic motivation and extrinsic motivation, both of which are veri influential in a learning process. Intrinsic motivation is found in students because of the spririt and ideals to be achieved and extrinsic motivation given by teachers, parents, friends and the environment can improve student learning outcomes. The teacher’s efforts in maintaining the quality of learning motivation on students’ listening skills by providing video, motivatonal words before strating learning, and providing active and fun learning